Environmental Stewardship Crisis in Eco-Pastoral Studies - Situmorang, Meditatio; Saragih, Ratna; Gultom, Rida; Purba, Hendra Putra (LPPM IAKN Tarutung, 2023)
The aim of this research is to examine ecology from a pastoral perspective. The methodology used in this research is the phenomenological method. Using this method, researchers examine natural damage from a pastoral perspective. Saving the environment will turn the center of human life upside down. The life of faith is moving from being centered on humans, centered on religious institutions, and now ecology is the center of attention. Ecological theology coupled with ecofeminism is a blessing for the environment. This theology brings enlightenment, liberation, and healing. Enlightening, liberating and healing in a pastoral perspective.